(untitled) (Revista de Estudos da Linguagem, 2020)
Abstract: Almost forty years ago, the proposal of the Conceptual Metaphor Theory represented a milestone for Cognitive Linguistics studies. From this point, many pieces of research were developed around the analytical category of metaphor. However, the majority of these papers are still in the monomodal field, intending to build a concept resulting from the source and target domains that come specifically from the verbal structures. Taking this into consideration, this paper intends to focus on the metaphorical occurrence in diverse semiotic modes that constitute multimodal texts. In order to fulfill this aim, we outlined a corpus of five editorial cartoons about “fake news”. Our specific objective is to, making use of the concept of multimodal metaphors proposed by Forceville (1996, 2009), presented how the different semiotic modes, in this case the verbal and the visual ones, are interwoven in the building of these metaphors. In this way, in our study, besides validating the thesis proposed by Forceville (2009) about the occurrence of metaphors not only in the verbal mode, it was also possible to verify the importance of multimodal metaphors for the meaning construction process in the analyzed genre. Keywords: metaphors; multimodal metaphors; fake news. Resumo: Há quase quarenta anos atrás um marco nos estudos da Linguística Cognitiva, em especial em sua semântica, ocorreu: a proposta da Teoria da Metáfora Conceitual. A partir desse trabalho, muitas pesquisas foram desenvolvidas em torno da categoria analítica da metáfora. Porém, grande parte desses trabalhos ainda encontra-se no campo dos denominados textos monomodais, visando apenas a construção conceitual resultante de domínios fonte e alvo oriundos especificamente do modo verbal. Diante disso, o presente artigo propõe-se a promover um trabalho dedicado à ocorrência metafórica nos diferentes modos semióticos que constituem os textos multimodais. Para cumprirmos tal objetivo, delineamos como corpus cinco charges que versam sobre o conceito fake news. Nosso objetivo específico consiste em apresentar, através do conceito de metáforas multimodais, proposto por Forceville (1996, 2009), a forma pela qual diferentes modos semióticos, nesse caso em especial o verbal e o imagético, imbricaram-se na construção dessas metáforas. Assim, em nosso estudo, além de vislumbrarmos a validação da proposição de Forceville (2009) sobre a não ocorrência do processo metafórico apenas no modo verbal, foi possível a verificação da importância das metáforas multimodais para a construção dos sentidos do gênero em análise. Palavras-chave: metáforas; metáfora multimodal; fake news.